Caffeine consumption amongst British athletes following changes to the 2004 WADA prohibited list - Chester, N.; Wojek, N. (International Journal of Sports Medicine, 2008)
This study was undertaken to examine self-reported caffeine consumption and reasons for its use, amongst UK athletes, following its removal from the 2004 World Anti-Doping Agency (WADA) Prohibited List. A convenience sample of track and field athletes (n = 193) and cyclists (n = 287) completed a postal or Web-based questionnaire. Messages were posted on athletics and cycling club Web sites and mailing lists to direct athletes to the Web-based questionnaire. Postal questionnaires were distributed at domestic sporting events. A higher proportion of cyclists (59.9 %) compared with track and field athletes (32.6 %) consumed caffeine to enhance performance (p < 0.001). A higher proportion of elite as opposed to sub-elite athletes representing cycling (p = 0.031) and athletics (p = 0.010) used caffeine to enhance performance. Of all caffeine containing products used, coffee, energy drinks, pharmaceutical preparations and caffeinated sports supplements were most prevalent. Results revealed that amongst UK athletes, the intention to use caffeine as an ergogenic aid was high, and that use was more widespread and accepted in competitive sport, especially at elite level, when compared to recreational sport.